Complete oxidation of hydroxymethylfurfural to furandicarboxylic acid by aryl-alcohol oxidase - Serrano, Ana; Calviño, Eva; Carro, Juan; Sánchez-Ruiz, María I.; Cañada, F. Javier; Martínez, Angel T. (Biotechnology for biofuels, 2019)
5-Hydroxymethylfurfural (HMF) is a highly valuable platform chemical that can be obtained from plant biomass carbohydrates. HMF can be oxidized to 2,5-furandicarboxylic acid (FDCA), which is used as a renewable substitute for the petroleum-based terephthalic acid in polymer production. Aryl-alcohol oxidase (AAO) from the white-rot fungus is able to oxidize HMF and its derivative 2,5-diformylfuran (DFF) producing formylfurancarboxylic acid (FFCA) thanks to its activity on benzylic alcohols and hydrated aldehydes. Here, we report the ability of AAO to produce FDCA from FFCA, opening up the possibility of full oxidation of HMF by this model enzyme. During HMF reactions, an inhibitory effect of the H O produced in the first two oxidation steps was found to be the cause of the lack of AAO activity on FFCA. In situ monitoring of the whole reaction by H-NMR confirmed the absence of any unstable dead-end products, undetected in the HPLC analyses, that could be responsible for the incomplete conversion. The deleterious effect of H O was confirmed by successful HMF conversion into FDCA when the AAO reaction was carried out in the presence of catalase. On the other hand, no H O formation was detected during the slow FFCA conversion by AAO in the absence of catalase, in contrast to typical oxidase reaction with HMF and DFF, suggesting an alternative mechanism as reported in some reactions of related flavo-oxidases. Moreover, several active-site AAO variants that yield nearly complete conversion in shorter reaction times than the wild-type enzyme have been identified. The use of catalase to remove H O from the reaction mixture leads to 99% conversion of HMF into FDCA by AAO and several improved variants, although the mechanism of peroxide inhibition of the AAO action on the aldehyde group of FFCA is not fully understood.